Women's Nutrition: Folate/Folic Acid - Caroline Dunn; Jeanette Andrade; Gail Kauwell (EDIS)
Folate/folic acid is necessary throughout the entire lifespan, and especially for women who can become pregnant because of its role in reducing the risk of birth defects. This article provides information about the folate/folic acid needs of women who can become pregnant including sources and strategies for meeting the recommended intake for birth defect risk reduction.